2014
DOI: 10.1292/jvms.14-0169
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Identification of Proteins Differentially Expressed in Response to Resveratrol Treatment in Middle Cerebral Artery Occlusion Stroke Model

Abstract: Resveratrol has a neuroprotective effect against cerebral ischemia. The objective of this study was to identify proteins that are differentially expressed in the cerebral cortex of vehicle- and resveratrol-treated animals during ischemic injury. Focal cerebral ischemia was induced as middle cerebral artery occlusion (MCAO) in male rats. Rats were treated with vehicle or resveratrol before MCAO, and cerebral cortex was collected 24 hr after MCAO. Cerebral cortex proteins were identified by two-dimensional gel e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
46
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(46 citation statements)
references
References 35 publications
(47 reference statements)
0
46
0
Order By: Relevance
“…IDH1 mutations were predominantly found in human low-grade astrocytoma, oligodendroglioma, and secondary GBM. On the other hand, IDH2 mutations occurred less frequently in gliomas and were mutually exclusive of IDH1 mutations [119]. RES has been found to maintain IDH levels in a middle cerebral artery occlusion stroke model [120] and to protect the left ventricle by increasing IDH activity in myocardial infarction [121].…”
Section: Resveratrol In Brain Cancer Studiesmentioning
confidence: 99%
“…IDH1 mutations were predominantly found in human low-grade astrocytoma, oligodendroglioma, and secondary GBM. On the other hand, IDH2 mutations occurred less frequently in gliomas and were mutually exclusive of IDH1 mutations [119]. RES has been found to maintain IDH levels in a middle cerebral artery occlusion stroke model [120] and to protect the left ventricle by increasing IDH activity in myocardial infarction [121].…”
Section: Resveratrol In Brain Cancer Studiesmentioning
confidence: 99%
“…In addition, resveratrol protects rat brain from cerebral ischemic injury via a sirtuin 1-uncoupling protein 2 and TRPC6/CREB pathways (7,16). Resveratrol also regulates the expression of various proteins associated with oxidative stress and energy metabolism in focal cerebral ischemia (25). Furthermore, resveratrol can enhance the neuroprotection when coadministrated with lipoic acid in cerebral ischemia (24).…”
Section: A B C Dmentioning
confidence: 99%
“…Resveratrol alleviated MCAO-induced neurological behavior deficits. Moreover, our previous study has been shown that resveratrol regulates the expression of various proteins that associated with oxidative stress in focal cerebral ischemia [26].…”
Section: Discussionmentioning
confidence: 93%
“…Animals were divided into the following four groups: vehicle + sham, resveratrol + sham, vehicle + MCAO, and resveratrol + MCAO (8 rats per group). Resveratrol (30 mg/kg, Sigma-Aldrich, St. Louis, MO, USA) was dissolved in 0.05% dimethyl sulfoxide (DMSO; Sigma-Aldrich) in phosphate buffered saline and immediately intraperitoneally injected [26]. Vehicle-treated animals were injected with only DMSO solution without resveratrol.…”
Section: Experimental Animalsmentioning
confidence: 99%